Democratic Republic of the Congo (DRC) Micronutrient Cross-Sectional Household Survey - University of British Columbia; International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Democratic Republic of the Congo (DRC) Micronutrient Cross-Sectional Household Survey is a comprehensive nutritional survey among women (18–45 years) and their children (6–59 months) in the South Kivu and Kongo Central Provinces of the Democratic Republic of Congo (DRC). The survey was conducted to assess the prevalence of anemia and micronutrient deficiencies among women of childbearing age and children under five years of age. In this cross-sectional survey, 744 mother-child pairs were recruited using a probability proportionate to size (PPS) sampling method in select health zones of South Kivu and the rural district of Lukaya in Kongo Central, DRC between June and October 2014. This dataset includes information on household's socio-economic characteristics; water, sanitation and hygiene practices; child health and health-seeking behavior; and consumption of bean. Anthropometric measurements were taken by trained personnel using the Food and Nutrition Technical Assistance (FANTA) Anthropometric Indicators Measurement Guide.